Mental Health Counselling, Introduction to Information & Communication Technology (ICT), and Understanding Casual English Vocabulary for Students of Junior High School 66 Jakarta - Rizky Prasetya; Achmad Syarif; Saskia Lydiani (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Mental health can affect language learning outcomes as it impacts students’ ability to focus, process information, and retain knowledge. Stress, anxiety, and depression can adversely affect a student’s language learning abilities. Thus, providing mental health counseling can effectively promote students’ mental well-being and improve their language learning outcomes. The activities promoted mental well-being, Enhanced language learning outcomes, Improved communication skills, Encouraged community engagement, and Developed life skills. The activities method implements the offline seminar. A seminar can still be a valuable delivery method for introducing these topics and raising awareness among students, teachers, and the wider community. It can be a platform for discussion and engagement, allowing students to ask questions and share their thoughts and experiences. The results and outcomes are that students who receive mental health counseling may experience improvements in their mental health and well-being. They may develop better-coping mechanisms, improved self-awareness, and greater emotional resilience. Additionally, they may become more proficient in using technology to learn languages and gain greater exposure to and understanding of informal English vocabulary. Students with better mental health, language, and communication skills may be more successful in their studies and better prepared for future academic and professional endeavors. The activities can be far-reaching, affecting students’ mental health, language learning, communication skills, engagement and participation in school, and academic performance.